Prosthetic Application of Newly Experimental Modeling Wax with some Additives( Medical Grass Extract) - Nadira A Hatim; Amer A Taqa; Ahmad W Alubaidi (University of Mosul, College of Dentistry, 2012)
Aims of the study: preparation of a new experimental modeling wax from hard paraffin, beeswax, starch, and medical Grass Extract (olive oil) and study the linear thermal expansion and melting point properties of the prepared wax. Materials and Methods : The samples were prepared ( 30 samples) by mixing Iraqi natural waxes (hard paraffin and beeswax) with additives (starch and olive oil) using spe-cial percentages proportions determined according to this study and using mold prepared according to ADA specification No.24, and the melting range and thermal expansion of these samples measured then compared with commercial modeling wax (SHANGCHI). Results: The new experimental model-ing wax 1 ( 80% hard paraffin + 15% beeswax + 5% olive oil) have minimum and maximum melting point mean value (59.8 - 63.6 °c) near to control (commercial modeling wax) (58 -63.4 °c) and the new experimental modeling wax 2 (90% beeswax + 5% starch + 5% olive oil) have linear thermal expan-sion mean value (0.186%) near to control (SHANGCHI) (commercial modeling wax) (0.204%). Con-clusions : The addition of olive oil to new experimental modeling wax 1(80% hard paraffin + 15% beeswax + 5% olive oil) lead to increase the linear thermal expansion and reduce the melting point, and the addition of olive oil to new experimental modeling wax 2 (90% beeswax + 5% starch + 5% olive oil) lead to decrease thermal expansion and reduce melting point.